Doctors in the East: Where West Meets East - Ho, Tak Ming
Chinese medicine has a 3000-year tradition. In the first millennium BC, systematic medical education had already begun and the state medical services were already well organised. A Chinese doctor performed surgery using Indian hemp as anaesthesia in the second century AD. In their search for the elixir of immortality, Taoist doctors laid the foundation for modern pharmaceutics. During the Sung dynasty (960-1279) Chinese medicine was on the threshold of greatness. However, the Renaissance did not happen in Sung China but in Europe three centuries later. When Western medicine was introduced in China during the Ch'ing dynasty (1644-1911), there was inevitably a clash of cultures. Western-trained doctors began to dominate the medical scene, and Chinese medicine appeared to have met its demise. In the last half-century, however, like the mythical phoenix, Chinese medicine has made a reappearance. Will a bold new partnership, a synthesis of West and East, modern and traditional, transform global medicine in the new millennium?